ECTHR_COMMITTEE 41468/10 vom 8. November 2016 , AFFAIRE GUTĂU c. ROUMANIE - Ecthr Committee (2016)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure pénale;Article 6-1 - Procès équitable); Violation: 6;6-1